Management and evolution of the European Union member states in the Big Data era. The impact of Big Data on the organization of the European market - Constantin, Anghelache (De Gruyter, 2020)
The inclusion of "Big Data" in financial markets accelerates the speed of decision-making and boosts stock markets. The appearance of virtual currencies is concomitant to the management of "Big Data" and secures transactions via the Blockchain. New behaviors are observed on the markets thanks to algorithmic optimizations or via the technology of the "Blockchain". Commercial markets are impacted by the fact that market analysis, through Big Data, challenges traditional approaches to marketing. "Big Data", because of fast, real-time analysis and the use of data of various natures, allows a better decision-making whether it is in the medical field or in the taxation of countries. The use of internet tools places the customer or employees in direct contact with organizations and companies. The mass processing of all these large amounts of data requires computer or robotic tools whose raw material to work is energy. The data collection tools require co-operation directly with individuals and social groups. This induces important changes in the ways of acting or even designing services with the actors. Due to the large volume of processed data, the data analysis is refined and allows calculations with very large data volumes using new specific methods. The speed of data processing is facilitated by the participation of the individual or social groups in the sense that the collection of data enriches the "Big Data" while respecting the authorization given by the citizen/client. The variety of data makes it possible to improve medical diagnoses and help to set up prevention policies that are less costly than healthcare policies This does not fail to question the citizen/client as to his responsibility vis-